2021
DOI: 10.32942/osf.io/rty9q
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mobbing in animals: a thorough review and proposed future directions

Abstract: Mobbing is an important anti-predator behavior where prey harass and attack a predator to lower the immediate and long-term risk posed by predators, warn others, and communicate about the predator’s threat. While this behavior has been of interest to humans since antiquity, and aspects of it have been well researched for the past 50 years, we still know little about its ecology and the evolutionary pressures that gave rise to this ubiquitous anti- predator behavior. In this review, we explore what mobbing is, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 160 publications
(254 reference statements)
0
1
0
Order By: Relevance
“…A two-year observational study of squirrels, for instance, found that vocalizations served a dual function of deterring predators and warning offspring (Burnett & Koprowski, 2020). Predator harassment, termed mobbing, is also widespread across species and typically involves vocalizations (Carlson & Griesser, 2021).…”
Section: Pursuit Deterrencementioning
confidence: 99%
“…A two-year observational study of squirrels, for instance, found that vocalizations served a dual function of deterring predators and warning offspring (Burnett & Koprowski, 2020). Predator harassment, termed mobbing, is also widespread across species and typically involves vocalizations (Carlson & Griesser, 2021).…”
Section: Pursuit Deterrencementioning
confidence: 99%